RESPON TANAMAN KACANG PANJANG (Vignasinensis L.) PADA BERBAGAI DOSIS PUPUK KOMPOS DARI KULIT BUAH KAKAO - Josina Irene Brigetha Hutubessy; Kristono Y. Fowo; Doris Krisanto Paso (AGRICA, 2021)
Response of Long Beans (Vigna sinensis L.) Due to Dosage Treatment of Compost Fertilizer from Cocoa Fruit Peel. The research was conducted in the Experimental Garden of the Faculty of Agriculture, University of Flores, Lokoboko Village, Ndona District, Ende Regency from June to August 2020. The purpose of this study was to determine the effect of cocoa husk fertilizer dose on the growth and yield of long beans. Using Randomized Block Design (RAK). With 5 doses of cocoa pod compost, namely: D1 : without treatment of cocoa pod skin or 0 g/plant, D2 : 5 tons per hectare of cocoa pod compost, D3 : 7.5 tons per hectare of cocoa pod compost, D4 : 10 tons per hectare of cocoa pod compost. D5 : 12.5 tons per hectare of cocoa pod husk compost. Each treatment was repeated 4 times, so that 20 trials were obtained. The application of cocoa husk compost fertilizer on long bean plants was proven to have a very significant effect on increasing the number of leaves at the observational ages of 21, 28 and 35 days after planting, leaf area at planting ages 14, 21, 28 and 35 days after planting, number of fruits, fruit weight at planting and weight. fruit per hectare The optimal dose of cocoa pod compost for long bean plants is 250gr per plant or the equivalent of 12.5 tons per hectare (D5) which is able to provide optimal growth and yield of long bean plants with an average percentage increase in the number of leaves aged 21, 28 and 35 by 20.68%; the mean leaf area at the age of 14, 21, 28 and 35 hst was 18.23%, the number of fruit was 27.57%; fruit weight per plant was 36.81% and fruit weight per hectare was 36.81%. Response of Long Beans (Vigna sinensis L.) Due to Dosage Treatment of Compost Fertilizer from Cocoa Fruit Peel. The research was conducted in the Experimental Garden of the Faculty of Agriculture, University of Flores, Lokoboko Village, Ndona District, Ende Regency from June to August 2020. The purpose of this study was to determine the effect of cocoa husk fertilizer dose on the growth and yield of long beans. Using Randomized Block Design (RAK). With 5 doses of cocoa pod compost, namely: D1 : without treatment of cocoa pod skin or 0 g/plant, D2 : 5 tons per hectare of cocoa pod compost, D3 : 7.5 tons per hectare of cocoa pod compost, D4 : 10 tons per hectare of cocoa pod compost. D5 : 12.5 tons per hectare of cocoa pod husk compost. Each treatment was repeated 4 times, so that 20 trials were obtained. The application of cocoa husk compost fertilizer on long bean plants was proven to have a very significant effect on increasing the number of leaves at the observational ages of 21, 28 and 35 days after planting, leaf area at planting ages 14, 21, 28 and 35 days after planting, number of fruits, fruit weight at planting and weight. fruit per hectare The optimal dose of cocoa pod compost for long bean plants is 250gr per plant or the equivalent of 12.5 tons per hectare (D5) which is able to provide optimal growth and yield of long bean plants with an average percentage increase in the number of leaves aged 21, 28 and 35 by 20.68%; the mean leaf area at the age of 14, 21, 28 and 35 hst was 18.23%, the number of fruit was 27.57%; fruit weight per plant was 36.81% and fruit weight per hectare was 36.81%.